Differential Diagnosis Value of Neutrophil Gelatinase Associated Lipocalin as a Noninvasive Biomarker in Perianal Fistulizing Crohn’s Disease - Ma K; Li Y; Wu J; Fu Y; Yin L; Xu S; Weng F; Yao Y; Wang C (Journal of Inflammation Research)
Kai Ma,* Yikun Li,* Jingwen Wu, Yi Fu, Lu Yin, Simin Xu, Feiyang Weng, Yibo Yao, Chen Wang Department of Proctology, Longhua Hospital, Shanghai University of Traditional Chinese Medicine, Shanghai, 200032, People’s Republic of China*These authors contributed equally to this workCorrespondence: Chen Wang; Yibo Yao, Department of Proctology, Longhua Hospital, Shanghai University of Traditional Chinese Medicine, Shanghai, 200032, People’s Republic of China, Email wangchen_longhua@163.com; elevenzoe@163.comBackground: Diagnosing perianal fistulizing Crohn’s disease (pfCD) typically depends on costly and time-intensive endoscopic and radiographic procedures. Compelling evidence indicates that neutrophil gelatinase-associated lipocalin (NGAL) plays a role in the pathophysiology of Crohn’s disease (CD) and may serve as a noninvasive biomarker for its diagnosis. This study aimed to evaluate NGAL’s potential as a noninvasive diagnostic biomarker between pfCD and cryptoglandular (CG) perianal fistula, and its correlation with disease severity in pfCD.Methods: Serum, fecal, and fistula tissue samples were collected from 96 patients with pfCD and 97 patients with CG perianal fistula as controls. Serum NGAL levels were quantified through ELISA and fistula tissue NGAL levels were quantified through immunohistochemical staining, while pfCD disease severity was evaluated using the Crohn’s Disease Activity Index (CDAI) and Perianal Disease Activity Index (PDAI). Additional laboratory parameters, including NGAL, fecal calprotectin (FC), C-reactive protein (CRP), and erythrocyte sedimentation rate (ESR), were analyzed, and their correlations were assessed. Receiver operating characteristic (ROC) analysis was conducted to evaluate NGAL’s diagnostic potential for pfCD.Results: Levels of serum NGAL, FC, CRP, and ESR in patients with pfCD were significantly elevated compared to the control group (p < 0.001); Spearman correlation analysis indicated a positive correlation between serum NGAL and FC, CRP, ESR, CDAI, and PDAI scores. The area under the ROC curve (AUC) for serum NGAL in diagnosing pfCD was 0.927 (95% CI: 0.890– 0.964). The AUC for FC in diagnosing pfCD were 0.887 (95% CI: 0.839– 0.935). Additionally, serum and fistula tissue NGAL levels were positively correlated with disease complexity in pfCD according to the Montreal classification.Conclusion: These findings suggest that serum NGAL is associated with pfCD severity and may offer a promising noninvasive biomarker for diagnosing and assessing pfCD.Keywords: neutrophil gelatinase associated lipocalin, perianal fistulizing Crohn’s disease, biomarker, diagnosis value